Pemberdayaan masyarakat dalam peningkatan produktifitas pancake durian di Dusun Gondang Desa Purworejo Kecamatan Candimulyo Kabupaten Magelang - Muna, Nadia Isnal; Farikhah, Kuni; Sa’adiah, Siti Khalimatus; Shofa, Salsabila Naila; Kusumaningtyas, Juwita Artanti (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Community empowerment is increasing the dignity of certain groups of citizens in poverty and underdevelopment conditions, as well as strengthening social capital in community groups, to make them more productive and avoid less productive habits. This research aims to increase the productivity of the Gondang Hamlet community in utilizing existing commodities by processing durian into durian pancakes carried out in the Gondang Hamlet community, Purworejo Village, Candimulyo District, Magelang Regency. The research method used was the Participation Action Research (PAR) method, which was a collaborative approach that provided training in making durian pancakes to PKK cadres and yasinan women participants in Gondang hamlet, Purworejo village. The source of this research is based on the results of primary or secondary data. The results of the research concluded that in implementing community empowerment in increasing productivity through making durian pancakes, the participation of the Gondang Hamlet community is needed to carry out the practice of making it and the community's willingness to develop knowledge of the practice of making it.